UTILIZATION OF INSTAGRAM SOCIAL MEDIA IN DELIVERING ISLAMIC CHARACTER EDUCATION CONTENT AT IT KHAIRUL IMAM HIGH SCHOOL - Muthya Khairunnisa; Mahariah Mahariah (Institut Agama Islam Negeri (IAIN) Curup, 2026)
The rapid development of digital media has triggered a conflict between positive effects, such as easy access to knowledge, and negative effects such as moral decline and gadget addiction in students' mindsets. This dilemma demands an adaptive transformation of Islamic character education to strengthen the morals of the younger generation directly in cyberspace. Therefore, this study aims to test the effectiveness of the Instagram platform as a means of delivering Islamic character education content at SMA IT Khairul Imam. This study used a qualitative approach with descriptive methods through observation, interviews, and documentation techniques, involving the principal, Islamic Religious Education teachers, student activity coordinators, the student council media team, and students. The results show that Instagram is used as a medium to convey Islamic values ​​through engaging visual content such as educational videos, moral campaigns, and documentation of religious activities. The published content contains values ​​of religiosity, responsibility, and etiquette in daily life. Furthermore, the publication process also goes through a monitoring stage to ensure it remains in accordance with Islamic norms and teachings. Thus, these findings demonstrate the importance of social media such as Instagram as an effective means to support the formation of Islamic character in students in a more contextual and engaging manner.